Arterial Stiffness and Dialysis Calcium Concentration - Fabrice Mac-Way; Amélie Leboeuf; Mohsen Agharazii (International Journal of Nephrology)
Arterial stiffness is the major determinant of isolated systolic hypertension and increased pulse pressure. Aortic stiffness is also associated with increased cardiovascular morbidity and mortality in patients with chronic kidney disease, hypertension, and general population. Hemodynamically, arterial stiffness results in earlier aortic pulse wave reflection leading to increased cardiac workload and decreased myocardial perfusion. Although the clinical consequence of aortic stiffness has been clearly established, its pathophysiology in various clinical conditions still remains poorly understood. The aim of the present paper is to review the studies that have looked at the impact of dialysis calcium concentration on arterial stiffness. Overall, the results of small short-term studies suggest that higher dialysis calcium is associated with a transient but significant increase in arterial stiffness. This calcium dependant increase in arterial stiffness is potentially explained by increased vascular smooth muscle tone of the conduit arteries and is not solely explained by changes in mean blood pressure. However, the optimal DCa remains to be determined, and long term studies are required to evaluate its impact on the progression of arterial stiffness.